Transformasi Nilai Ḥalāl–Ṭayyib dalam Tafsir Indonesia: Kajian Historis dan Kontemporer - Rahma Nurul Latifah; M. Sihabudin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The rapid globalization of the food industry and the rising awareness of Muslim consumers have profoundly reshaped the interpretation of the Qur’anic concepts of ḥalāl and ṭayyib in Indonesia. While classical exegesis confined their meanings to legal permissibility and physical cleanliness, contemporary interpretations view ḥalāl–ṭayyib as multidimensional principles encompassing nutrition, health, ethical production, and environmental sustainability. This study aims to explore the transformation of Qur’anic interpretations of ḥalāl and ṭayyib from the classical to the contemporary period within the Indonesian exegetical tradition. Employing a qualitative library research design, it applies thematic content analysis to three major works: Marāḥ Labīd by Nawawī al-Bantanī, Al-Azhar by Hamka, and Al-Mishbāḥ by Quraish Shihab. The findings reveal a paradigmatic shift from a normative–legal framework to a contextual approach that integrates social, health, and ecological dimensions. This transformation reinforces the maqāṣid al-syarī‘ah (objectives of Islamic law) in the domain of consumption and provides a philosophical foundation for contemporary ḥalāl certification policies and the development of Indonesia’s modern ḥalāl industry.